Effective Project-Based Learning Strategies to Enhance Critical Thinking, Creativity, Communication, and Collaboration Skill - Almendo Thio Thio; C. Asri Budiningsih; Rishe Purnama Dewi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to explicitly examine the effectiveness of Project-Based Learning (PBL) strategies in enhancing students' 21st-century skills, particularly the 4Cs: critical thinking, creativity, communication, and collaboration. The research involved 30 ninth-grade students from a junior high school in BSD Tangerang, who served as the research subjects selected through purposive sampling. Using a descriptive qualitative approach, data were collected through document analysis, classroom observations, and interviews with teachers and students. The data were analyzed using the stages of data reduction, data display, and conclusion drawing, and supported by pretest and posttest comparisons to assess skill improvement. The findings revealed significant increases in students’ 4C skills after participating in various project-based activities such as group presentations, digital literacy projects, poster creation, and social projects. The results highlight the potential of PBL to foster both academic achievement and essential soft skills. These findings suggest that further research should explore the integration of PBL across different educational levels and disciplines to maximize its pedagogical impact in diverse learning contexts.